(untitled) (Al-Farooq Journal of Sciences, 2025)
This study aims to explore techniques or mechanisms that could enhance long-term retention in learning. Retention techniques like related vocabulary learning aim to enable learners to apply what they have learned in the long-term retention to practice. However, little literature focused on the differences in vocabulary-related retention techniques. This study aims to explore the differences in memory-based retention techniques in the field of vocabulary learning. This will be fulfilled by reviewing the differences of the memory corner and word’s corner, and the relationship between different linguistic dimensions including vocabulary size, productive knowledge, receptive knowledge, and vocabulary-related retention techniques